2021
DOI: 10.1186/s12889-021-10257-2
|View full text |Cite
|
Sign up to set email alerts
|

How did governmental interventions affect the spread of COVID-19 in European countries?

Abstract: Background To reduce the transmission of the severe acute respiratory syndrome coronavirus 2 in its first wave, European governments have implemented successive measures to encourage social distancing. However, it remained unclear how effectively measures reduced the spread of the virus. We examined how the effective-contact rate (ECR), the mean number of daily contacts for an infectious individual to transmit the virus, among European citizens evolved during this wave over the period with impl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 27 publications
1
27
0
5
Order By: Relevance
“…Subsequently, this study determined that China's early government response had a sustained impact on the COVID-19 infection rate. Although previous studies are consistent with the findings of Post et al that the point of change in the daily effective contact rate overlapped with the moment of government response [14], Lai et al found that if the government's response had been implemented earlier, the number of COVID-19 cases could have been reduced [4]. Other scholars have analysed the impact of strict quarantine measures versus reopening public places on the early spread of COVID-19 [58], including COVID-19 infection and mortality rates [17,19,[58][59][60][61][62].…”
Section: Discussionsupporting
confidence: 90%
“…Subsequently, this study determined that China's early government response had a sustained impact on the COVID-19 infection rate. Although previous studies are consistent with the findings of Post et al that the point of change in the daily effective contact rate overlapped with the moment of government response [14], Lai et al found that if the government's response had been implemented earlier, the number of COVID-19 cases could have been reduced [4]. Other scholars have analysed the impact of strict quarantine measures versus reopening public places on the early spread of COVID-19 [58], including COVID-19 infection and mortality rates [17,19,[58][59][60][61][62].…”
Section: Discussionsupporting
confidence: 90%
“…In a recent systematic review of observational studies analysing school closing and reopening Walsh et al 59 found that half of the studies with lower risk of bias concluded that school closing reduced community transmission while half of the studies found no effect. Other analyses 60 , 61 , 62 , 63 , 64 , 65 suggest that school closingmay have been a more important factor during the first wave of the COVID-19 epidemic than initially thought. As the epidemiological situation has improved, reopening schools has become imperative.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies show that a high percentage of reduced contacts through social isolation limits the spread of new cases [39] , [47] . The timing of enforcing lockdown restrictions is also crucial, with earlier implementations leading to lesser infections [3] , [5] . The present study also agrees with these results.…”
Section: Resultsmentioning
confidence: 99%
“…Stringent implementation of healthcare advisories from WHO, strategies such as national lockdowns [2] , [3] and effective interventions by Governments in testing, isolating and treating the infected aided to control the spread of the virus in its first wave [4] , [5] , [6] . Nevertheless, the viral pandemic affected human life and the global economy in an adverse manner [7] .…”
Section: Introductionmentioning
confidence: 99%